Numerical analysis and comparison study of the 1:60 scaled DTU 10 MW TLP floating wind turbine. (January 2023) - Kim, T.; Madsen, F.J.; Bredmose, H.; Pegalajar-Jurado, A.
Abstract: This paper presents numerical investigations and comparison to experiments for a scaled DTU 10MW Tension Leg Platform (TLP) floating wind turbine. Two state-of-the-art aero-servo-hydro-elastic models, HAWC2 and FAST, are used and compared with experimental results. This study applies the same controller, turbulent wind, and hydrodynamic input as in the experiments to the numerical simulations. First, detailed numerical model calibration and validation have been performed. Free decay experimental test results are compared. Next, the damping ratio is calibrated. The rotor thrust is matched to the measurements by adjustment of the blade pitch angle in both numerical models. The same controller used in the experiments is applied to the numerical model via a Dynamic Link Library interface. Detailed comparisons for regular waves, irregular waves, and a focused wave group impact are presented. Results for surge motion, nacelle acceleration, front mooring line tension, blade pitch and rotor speed are included. In general, both numerical models predict the floating wind turbine responses very well compared to the experimental results both in time and frequency domains. Owing to the use of a linear wave forcing model and Morison based viscous loads, however, the low-frequency surge motion is found to be under-predicted in both models. Highlights: Numerical re-simulation of TLP with same active controller used in experiments Numerical re-simulation of TLP with same environmental wind and wave conditions HAWC2 and FAST predict the TLP responses very well in time and frequency domain Importance of the 2nd order potential flow effect to capture nonlinear forcing